A ternary block polymer modified nanofiltration membrane and a preparation method thereof

CN117323821BActive Publication Date: 2026-10-20TAIZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311486247.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-09
Publication Date
2026-10-20
Estimated Expiration
2043-11-09

AI Technical Summary

Technical Problem

膜分离技术的应用优势显著,但是目前作为新兴技术,还有许多不足:第一,已知的膜材料较少,膜孔径分布不均,分离能力有限

Benefits of technology

[0023]本发明通过顺序加料诱导自组装成功合成了具有三元嵌段结构的聚合物聚异戊二烯-b-聚苯乙烯-b-聚2-丙烯酰胺基-2-甲基丙磺酸钠盐。三元嵌段聚合物复合改性纳滤膜与原PVDF滤孔膜相比渗透选择性和稳定性提高,膜孔径减小,可实现100nm的纳米孔径。在猪脾脏浆液分离提纯脾氨肽等活性物质的应用研究中,三元嵌段聚合物处理过的PVDF纳滤膜可以实现多肽等物质的分离提纯。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117323821B_ABST
    Figure CN117323821B_ABST
Patent Text Reader

Abstract

The application provides a kind of ternary block polymer modified nanofiltration membrane and its preparation method, with azobisdimethylvaleronitrile as initiator, N, N-dimethylformamide as solvent, 2-acrylamide-2-methylpropanesulfonic acid sodium salt, styrene, isoprene as monomer, by sequential feeding first let styrene and 2-acrylamide-2-methylpropanesulfonic acid sodium salt copolymerization, then join isoprene monomer to participate in polymerization self-assembly, obtain ternary block polymer. The ternary block structure polymer obtained is prepared into composite nanofiltration membrane on PVDF filter hole membrane by coating method. Compared with the original PVDF filter hole membrane, the permeation selectivity and stability of the ternary block polymer composite modified nanofiltration membrane are improved, the membrane pore size is reduced, and a nanometer pore size of 100 nm can be realized. In the application research of separating and purifying active substances such as spleen amino acid in pig spleen plasma, the PVDF nanofiltration membrane treated by the ternary block polymer can realize the separation and purification of polypeptides and other substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanofiltration membrane technology and relates to a ternary block polymer modified nanofiltration membrane and its preparation method. Background Technology

[0002] With the rapid development of science and technology, biotechnology applications are becoming increasingly widespread, and the requirements for product purity in fields such as pharmaceuticals and food are gradually upgrading. Membrane separation technology, which emerged in the early 20th century, can achieve the separation and concentration of substances at room temperature, ensuring product quality and purity. It involves no phase change heat, has high adaptability, and is suitable for heat-sensitive substances and natural bioactive components. In biopharmaceutical applications, its advantages of high efficiency and simple operation have made it a major separation technology. Initially applied to liquid phase separation, it replaced many traditional distillation and rectification processes, resulting in products with higher purity and better stability. Membrane separation technology is essentially similar to sieving, mainly utilizing the concentration difference, pressure difference, potential difference, or temperature difference across the membrane to selectively separate, purify, and concentrate various components in a solution. It has advantages such as high separation accuracy, ease of operation, low energy consumption, wide application range, no phase change, and no pollution, and is applied in many industries. Countries worldwide are focusing on supporting the research and development of this technology. While membrane separation technology has significant advantages, as an emerging technology, it still has many shortcomings: First, the known membrane materials are limited, the membrane pore size distribution is uneven, and the separation capacity is limited. Secondly, membrane fouling is difficult to avoid due to the complexity of the material composition and viscosity, which exacerbates the separation effect. To address these issues, the selection and design of membrane materials has become a research hotspot, with nanofiltration membranes receiving particular attention due to their high selectivity and high separation precision. Common pressure-driven membrane separation technologies include microfiltration (MF), ultrafiltration (UF), nanofiltration (NF), and reverse osmosis (RO). Among these, nanofiltration's filtration precision falls between that of ultrafiltration and reverse osmosis, and it has two significant characteristics: first, it can retain solutes with molecular weights of 200–1000 Da; second, it is charged, exhibiting significant retention effects on inorganic salts and polyvalent ions. In particular, nanofiltration is more efficient than reverse osmosis in retaining low concentrations of divalent ions and small molecular weight substances. Therefore, nanofiltration is commonly used in the purification and separation of active pharmaceutical ingredients and wastewater treatment. The separation mechanism of nanofiltration membranes mainly includes electrostatic repulsion and steric hindrance effects. The differences in solute size and pore size, as well as the charge properties of the membrane surface, work synergistically to influence the separation effect of nanofiltration membranes. The development of nanofiltration membrane technology has led to increasingly sophisticated and diverse membrane materials and separators. However, many problems still need to be solved in practical applications. As the core of membrane separation technology, the membrane itself is a thin adsorption surface, easily susceptible to fouling. Membrane materials and preparation methods affect membrane lifespan and fouling levels. Membrane fouling refers to reversible and irreversible changes in membrane flux, rejection rate, and pore size, primarily caused by the deposition of substances that clog the membrane pores, resulting in a decrease in membrane flux. Therefore, improving membrane materials, refining preparation conditions, and designing and developing novel high-efficiency nanofiltration membranes are crucial for promoting the application of nanofiltration technology in biopharmaceuticals.

[0003] Block copolymers possess unique advantages in constructing nanomaterials, and their diverse structural morphologies have become a research hotspot in drug sustained release and catalytic reactions. Based on the self-assembly of block copolymers, nanostructured membranes with tunable pore sizes can be prepared. Developing block copolymer systems with designable structures and good stability is a current research goal. Common examples are amphiphilic block copolymers polymerized from two or more monomers, such as ABA and ABC types. In the synthesis of triblock polymers, the incompatibility between monomers leads to phase separation, which can ultimately form microphase-separated regions, reaching the nanoscale, due to the constraint of covalent bonds. However, as the polymer solubility increases and the hydrophobic segments repel water, the polymer chains self-assemble to form thermodynamically stable structures. Polymerization-induced self-assembly (PISA) has emerged, combining the preparation of nanomaterials with the synthesis of block polymers. It allows for intermittent, semi-continuous, or continuous feeding, mild reaction conditions, and the absence of metal components. It can be used for solution polymerization, emulsion polymerization, dispersion polymerization, etc. The organic compound polymerization reaction is simple to operate, and the molecular weight and distribution can be designed, allowing for the preparation of polymers with various structures such as block and grafted polymers. Typically, azobisisobutyronitrile (AIBN) initiators are used to generate free radicals that initiate the formation of primary free radicals from monomers. These primary free radicals then add to the monomers. The newly generated growing chain free radicals can initiate the formation of other monomers, effectively reducing side reactions such as bimolecular termination and achieving different molecular structures. Commonly applicable monomers include styrene and acrylates. With the development of heterogeneous polymerization research, combining it with dispersion polymerization systems has become one of the methods for preparing multi-component block polymers. Often, due to the growth of hydrophobic segments, a hydrophilic-hydrophobic equilibrium is eventually reached in the polymer, leading to self-assembly and the formation of block polymers with various morphologies. Block polymers often self-assemble to form nanoscale structures. Factors influencing these structures include polymer composition, molecular weight, concentration, pH, and temperature. Weiss et al., through RAFT polymerization, prepared triblock polymers that exhibited aggregated states based on different block sequences. Sumerlin et al. studied the effect of pH on the self-assembly of diblock polymers of sodium 2-acrylamido-2-methylpropanesulfonate and sodium 3-acrylamido-3-methylbutyrate, showing that micelles formed at pH below 5.5. Nakai et al., through RAFT polymerization, prepared diblock polymers of 2-methacryloyloxyethyl phosphocholine with cationic methacryloylpropyltrimethylammonium chloride and anionic AMPS, which formed vesicles in saline solution. Polyvinylidene fluoride (PVDF) membranes, widely used for their pore structure, possess certain mechanical strength, good thermal stability, and chemical resistance. However, their hydrophobicity limits their applications. Currently, it is known that modifying PVDF membranes with amphiphilic block polymers can improve stability and hydrophilicity, and further preparation of composite nanofiltration membranes is possible.

[0004] 2-Acrylamido-2-methylpropanesulfonic acid (AMPS) is commonly used as a sulfonate monomer with strong temperature and salt resistance, and has been industrialized in the domestic water treatment and oilfield fields. AMPS is readily soluble in water and dimethylformamide, non-polluting, and contains active unsaturated double bonds, readily undergoing self-polymerization and addition reactions with other olefin monomers. Its sulfonic acid groups are highly hydrophilic, providing temperature and salt resistance. Furthermore, AMPS has large side chains, enhancing the rigidity of the polymer backbone and increasing thermal stability. AMPS polymerizes readily in aqueous solutions, but sodium 2-acrylamido-2-methylpropanesulfonic acid can stably participate in polymerization in aqueous solutions. Economically, copolymers of AMPS with other monomers have greater application value, improving temperature resistance, salt resistance, and water dispersibility. Ren Yi et al. prepared the optimal monomer composition ratio of the ternary copolymer as DMAM:AMPS:AM = 2:20:78. The results showed that the tackifying property of the AM / AMPS / DMAM copolymer was significantly improved compared with that of the AM / AMPS copolymer and the AM / DMAM copolymer. The two functional monomers introduced played a complementary role.

[0005] This invention employs sequential feeding to induce self-assembly to synthesize a ternary block polymer of polyisoprene-b-polystyrene-b-poly2-acrylamido-2-methylpropanesulfonate sodium salt (PI-b-PS-b-PAMPS). The ternary block polymer is then composited with a PVDF filter membrane using a coating method to prepare a modified nanofiltration membrane. This process aims to achieve adjustable pore size and good stability in the nanofiltration membrane. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a ternary block polymer modified nanofiltration membrane and its preparation method.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a ternary block polymer modified nanofiltration membrane includes the following steps:

[0009] S1: A ternary block polymer was prepared using sodium 2-acrylamido-2-methylpropanesulfonate, styrene and isoprene as monomers, DMF as solvent and AIBN as initiator.

[0010] S2: A triblock polymer-ethanol mixed solution was prepared using a ternary block polymer as the solute and ethanol as the solvent; the PVDF microporous filter membrane was soaked in the solution and then naturally dried to obtain a ternary block polymer modified nanofiltration membrane.

[0011] Furthermore, in step S1, the molar ratio of styrene, isoprene, and sodium 2-acrylamido-2-methylpropanesulfonate is 1:1:0.1 to 0.8.

[0012] Furthermore, in step S1, the preparation of the ternary block polymer includes the following steps:

[0013] First, styrene, sodium 2-acrylamido-2-methylpropanesulfonate solution, AIBN and DMF are added for copolymerization. The mixture is stirred, refluxed, and reacted for 1-3 hours. Then, isoprene is added to participate in the copolymerization. The reaction is repeated for 1-3 hours. The steps are repeated more than twice. The resulting sample is cooled to room temperature to obtain a ternary block polymer solution.

[0014] Furthermore, in step S1, the stirring temperature is 60–85°C and the stirring speed is 10–30 rpm / min.

[0015] Furthermore, in step S2, the PVDF microporous filter membrane is a polarized PVDF microporous filter membrane.

[0016] Furthermore, in step S2, the concentration of the triblock polymer-ethanol mixed solution is 5-20%.

[0017] Furthermore, in step S2, the soaking time is 5 to 15 minutes; the natural drying time is 3 to 8 minutes.

[0018] A ternary block polymer-modified nanofiltration membrane was prepared using the above method.

[0019] The above-mentioned ternary block polymer modified nanofiltration membrane is used for the separation and purification of peptide substances.

[0020] Furthermore, the separation and purification steps include:

[0021] Pig spleen slurry is prepared by crushing, pulping and filtering pig spleen. The slurry is then separated and purified using a ternary block polymer modified nanofiltration membrane under operating conditions of 0.7-1.5 MPa and 1-40℃. After freeze drying, the corresponding spleen peptide powder is obtained.

[0022] The beneficial effects of this invention are as follows:

[0023] This invention successfully synthesized a ternary block polymer, polyisoprene-b-polystyrene-b-poly2-acrylamido-2-methylpropanesulfonate sodium salt, through sequential feeding-induced self-assembly. Compared to the original PVDF filter membrane, the ternary block polymer-modified nanofiltration membrane exhibits improved permeability selectivity and stability, and a smaller pore size, achieving a nanopore size of 100 nm. In application research for the separation and purification of active substances such as spleen peptides from porcine spleen serous fluid, the PVDF nanofiltration membrane treated with the ternary block polymer can achieve the separation and purification of peptides and other substances. Attached Figure Description

[0024] Figure 1 The infrared spectra of ternary block polymers with different monomer ratios in the embodiments of the present invention are shown.

[0025] Figure 2 n in the embodiments of the present invention St :n Ip :n AMPS Nuclear magnetic resonance spectra of ternary block polymers with a ratio of 1:1:0.1.

[0026] Figure 3 n in the embodiments of the present invention St :n Ip :n AMPS Nuclear magnetic resonance spectra of ternary block polymers with a ratio of 1:1:0.3.

[0027] Figure 4 n in the embodiments of the present invention St :n Ip :n AMPS Nuclear magnetic resonance spectra of ternary block polymers with a ratio of 1:1:0.5.

[0028] Figure 5 n in the embodiments of the present invention St :n Ip :n AMPS Nuclear magnetic resonance spectra of ternary block polymers with a ratio of 1:1:0.8.

[0029] Figure 6 The images shown are SEM images of polyvinylidene fluoride (PVDF) microporous filter membranes with different pore sizes in the embodiments of the present invention.

[0030] Figure 7 The images shown are SEM images of nanofiltration membranes with different concentrations in the embodiments of the present invention.

[0031] Figure 8 SEM images of nanofiltration membranes with different monomer ratios in embodiments of the present invention.

[0032] Figure 9 The images shown are SEM images of nanofiltration membranes with different immersion times in the embodiments of the present invention.

[0033] Figure 10 This is a mass spectrum of the spleen peptide powder in an embodiment of the present invention. Detailed Implementation

[0034] The technical solution of the present invention will be clearly and thoroughly described below with reference to the embodiments and accompanying drawings.

[0035] The experimental reagents used in this invention, such as N,N-dimethylformamide, styrene, isoprene, sodium 2-acrylamido-2-methylpropanesulfonate solution, and polyvinylidene fluoride microporous filter membrane, can all be purchased directly from the market. For example, in the embodiments of this invention, N,N-dimethylformamide (DMF, molecular formula C3H7NO), analytical grade, was provided by Sinopharm Chemical Reagent Co., Ltd.; styrene (ST, molecular formula C8H8), analytical grade, was provided by Shanghai Maclean Biochemical Technology Co., Ltd.; isoprene (C5H8), purity 99%, was provided by Shanghai Saen Chemical Technology Co., Ltd.; and sodium 2-acrylamido-2-methylpropanesulfonate solution (AMPS, molecular formula C7H7NO) was provided by Sinopharm Chemical Reagent Co., Ltd. 12 The NNaO4S, 50wt%, was provided by Shanghai Aladdin Biochemical Technology Co., Ltd.; the polyvinylidene fluoride microporous filter membrane (PVDF-II), with a nominal pore size of 0.1μm, was provided by Haiyan New Oriental Plastics Technology Co., Ltd.

[0036] Example

[0037] Table 1 Experimental formulation ratios

[0038]

[0039] Ternary block polymers were prepared using sodium 2-acrylamido-2-methylpropanesulfonate, styrene, and isoprene as monomers, DMF as solvent, and AIBN as initiator. The polymers were prepared by adding the DMF in three separate additions according to the formulation ratios designed in Table 1, such as n... St :n Ip :n AMPS When the ratio is 1:1:0.1, first add 0.01 mol styrene, 0.001 mol sodium 2-acrylamido-2-methylpropanesulfonate solution, 0.036 g AIBN and 30 ml DMF to a three-necked flask for copolymerization. In an 80°C constant temperature water bath, set the rotor stirring speed to 15 rpm / min, turn on reflux, and react for 2 hours. Then add 0.01 mol isoprene to participate in the copolymerization, react together for 2 hours, and repeat the above feeding sequence twice until the feeding step is finished. After the final 2 hours of reaction, allow the prepared sample to cool naturally to room temperature to obtain poly(styrene-2-acrylamido-2-methylpropanesulfonate-isoprene) mixtures with the four formulation ratios shown in Table 3. These mixtures are light yellow, transparent, and viscous. After removing the organic solvent DMF by pressure distillation, poly(styrene-2-acrylamido-2-methylpropanesulfonate-isoprene) is obtained.

[0040] Place the PVDF microporous filter membrane in a plasma cleaner, polarize both sides for three minutes, and then remove it for later use.

[0041] Composite nanofiltration membranes were prepared using a coating method, which is simple, rapid, and efficient. Using poly(styrene-2-acrylamido-2-methylpropanesulfonate sodium salt-isoprene) ternary block polymers with different molar ratios as the solute and ethanol as the solvent, triblock polymer-ethanol mixed solutions of different concentrations (5%, 10%, and 20%) were prepared. These solutions were then used to immerse polarized PVDF microporous membranes for 10 minutes, followed by 5 minutes of natural air drying. PVDF nanofiltration membranes with different concentrations and monomer ratios of triblock copolymers were prepared. Furthermore, by varying the number of immersion cycles, different types of PVDF nanofiltration membranes treated with triblock copolymers were obtained.

[0042] Pig spleen slurry is prepared by crushing, pulping, and filtering. The PVDF nanofiltration membrane is then treated with the triblock copolymer prepared above under the conditions of operating pressure 0.7-1.5 MPa and temperature 1-40℃ to separate and purify the pig spleen slurry. After freeze drying, the corresponding spleen peptide powder is obtained.

[0043] The structure of the ternary block polymer was determined using a Nicolet 5700 Fourier transform infrared spectrometer (Thermo Electron, USA). KBr pellets were used for sample preparation. The scanning resolution was 1 cm⁻¹. -1 Scanning range: 4000-400cm -1 .

[0044] The proton NMR spectrum of the polymer was detected using an AVANCEⅢHD 400 nuclear magnetic resonance spectrometer with DMSO-d6 as the solvent.

[0045] The distribution and pore size of the nanofiltration membrane surface pores were observed using an S-4800 scanning electron microscope at magnifications of 10K, 15K, 20K, and 200K.

[0046] Figure 1 Infrared spectra of poly(styrene-2-acrylamido-2-methylpropanesulfonate sodium salt-isoprene) triblock polymers with AMPS monomer ratios of 0.1, 0.3, 0.5, and 0.8. In the figure, 3450 cm⁻¹... -1 and 1640cm -1 These are the stretching vibration peaks of NH and CO in the amide group, respectively, and the peaks at 3000-2870 cm⁻¹. -1 CH stretching vibrations of saturated methyl and methylene groups, 1465-1340 cm⁻¹ -1 The peak value for CH bending vibration is 1675-1654 cm⁻¹. -1 It is a C=C stretching vibration, 1600-1450cm -1 The combined peaks represent the C=C skeletal vibration of the benzene ring, at 1390 cm⁻¹. -1It is the vibrational peak of the symmetrical methyl group, 1300-1010 cm⁻¹ -1 For CO stretching vibration, 1265-1045cm -1 Symmetrical and asymmetric vibrations of O=S=O, 765-680cm -1 For out-of-plane bending vibrations of hydrogen on a monosubstituted benzene ring, 627 cm⁻¹ -1 The peak at this point is the CS stretching peak in AMPS. As shown in the figure, the infrared spectrum of the triblock polymer corresponds to that of pure styrene, pure isoprene, and pure sodium 2-acrylamido-2-methylpropanesulfonate, indicating that the polymer contains segments of styrene, isoprene, and AMPS, and to a certain extent, the polymer has high reactivity and hydrophilicity.

[0047] Figure 2 The formula ratio is n St :n Ip :n AMPS The NMR spectrum of the triblock polymer with a ratio of 1:1:0.1 is shown. Five different hydrogen atoms are present in the spectrum, with the peak at chemical shift 2.5 representing the solvent peak of DMSO-d6. The lowest field singlet (δ at 7.98 ppm) originates from the amide group on AMPS, the singlet at 3.50 ppm from the methylene hydrogen bonded to the sulfonic acid group, the singlet at 2.90 ppm from -OCH2, and the singlet at 2.74 ppm from the -NCH2 group. The methyl group at the AMPS side chain is located at a peak of 1.43 ppm. The weak peaks between approximately 7.0-7.50 ppm and 5.0-6.0 ppm represent hydrogens on the benzene ring and vinyl group, respectively, indicating the possible presence of a small number of trans-1,4-polyisoprene. The absence of a prominent proton peak representing a double bond indicates that the monomers have completely reacted.

[0048] Figure 3 The formula ratio is n St :n Ip :n AMPS The NMR spectrum of the triblock polymer with a ratio of 1:1:0.3 is shown. Five types of hydrogen atoms exist in different environments, with the peak at chemical shift 2.5 representing the solvent peak of DMSO-d6. The peak integral area increases with increasing AMPS ratio. The weak peak at 8.4 ppm originates from the -OH group on the AMPS, the singlet at 7.95 ppm from the amide group on the AMPS, the singlet at 3.51 ppm from the methylene hydrogen linked to the sulfonic acid group, the singlet at 2.89 ppm from the -OCH2 group on the AMPS, the peak at 2.73 ppm from the -NCH2 group, and the peak at 1.45 ppm from the methyl group. Hydrogen atoms representing double bonds do not appear in the spectrum.

[0049] Figure 4 The formula ratio is nSt :n Ip :n AMPS The NMR spectrum of the triblock polymer with a ratio of 1:1:0.5 is shown. The spectrum contains five types of hydrogen atoms in different environments. The peak at chemical shift 2.5 represents the solvent peak of DMSO-d6. From low field to high field, the singlet at the lowest field (δ at 7.98 ppm) originates from the amide group of AMPS, the singlet at the highest field (δ at 1.45 ppm) originates from the side chain methyl group on AMPS, the peak at δ at 3.65 ppm originates from -CH2SO2 on AMPS, the singlet at δ at 2.92 ppm is -OCH2, the split peak at δ at 2.76 ppm is -NCH2, and the weak peak at approximately 6.15 ppm represents vinyl hydrogen.

[0050] Figure 5 The formula ratio is n St :n Ip :n AMPS The NMR spectrum of a triblock polymer with a ratio of 1:1:0.8 is shown. The spectrum contains five types of hydrogen atoms in different environments, with the solvent peak at chemical shift 2.5 being DMSO-d6. The integral curves of δ at 3.49 ppm and 1.45 ppm in the spectrum are compared to... Figure 2 , 3 The increasing trend of δ4 is more pronounced, indicating that the increase in the proportion of AMPS monomers affects the polymer structure. In the figure, the singlet at δ 7.96 ppm originates from the amide group on AMPS, the singlet at δ 3.49 ppm from the methylene hydrogen linked to the sulfonic acid group, the singlet at δ 2.90 ppm from the -OCH2 group on AMPS, the singlet at δ 2.74 ppm from the -NCH2 group, and the peak at δ 1.45 ppm from the methyl group at the side chain position of AMPS. The faintly visible weak peak between 5.5 and 6.3 ppm represents the presence of vinyl hydrogen after the 1,4 addition of isoprene monomer. The absence of a clearly defined peak representing a double bond indicates that all monomers have reacted.

[0051] Figure 6 SEM images of PVDF microporous filter membranes with different pore sizes are shown. The PVDF-II membrane has a pore size of 0.1 to 0.2 μm, a dense surface with fractured layers, and complex membrane channels, which is conducive to the adhesion of triblock copolymers and the formation of nanoscale pores.

[0052] Figure 7 (a) and (b) are composed of n St :n Ip :n AMPS The triblock polymer prepared by the formulation ratio of 1:1:0.3 was prepared into a 5% solution and soaked twice to obtain the SEM image of the nanofiltration membrane. Figure 7(c) and (d) are SEM images of nanofiltration membranes with a solution concentration of 20% while keeping the monomer ratio and number of soakings constant. Figure 7 Comparing (a) and (c), we can see that as the solution concentration increases, the fibers on the membrane surface thicken, the number of broken fibers decreases, the membrane pores become more intact, and the porosity significantly decreases. Especially from... Figure 7 In (b) and (d), it can be observed that the pore size of the nanofiltration membrane reaches approximately 100 nm when the solution concentration increases to 20%, while the pore size of the nanofiltration membrane with a solution concentration of 5% is around 250 nm. This indicates that increasing the content of the triblock polymer in the soaking solution is beneficial to reducing the pore size and resulting in smaller nanopores.

[0053] Figure 8 (a) and (b) are SEM images of nanofiltration membranes with AMPS monomer ratios of 0.3 and 0.5, respectively, under the condition that the solution concentration is 5% and the number of soaking times is 2. Figure 8 Images (c) and (d) are SEM images of nanofiltration membranes with AMPS monomer ratios of 0.3 and 0.5, respectively, under the same solution concentration of 20% and immersion cycles of 2. (Horizontal comparison) Figure 8 In (a) and (b), Figure 8 In (a), the separation between adjacent holes is not thorough enough, and the fibers are thin and weak. Figure 8 (b) The membrane pores are independent and intact, without any surface macropores containing deep micropores, and the diameter of the membrane pores is also relatively smaller compared to [previous examples]. Figure 8 The smaller the value of (a), the more stable the AMPS monomer becomes, indicating that a higher proportion of AMPS monomer results in smaller pore sizes. (Comparison) Figure 8 The same applies to (c) and (d). Figure 8 (d) has a clearly defined aperture, while Figure 8 (c) exhibits irregular pores with significant pore size variations, resulting in poor stability. However, further increasing the monomer ratio can lead to polymer blockage on the membrane surface or in the membrane channels. (Longitudinal comparison) Figure 8 In (a) and (c), as the solution concentration increases, the pores tend to become more defined, independent and dense due to the adhesion of more triblock polymers. Figure 8 Compared to (b), the pore size in (d) is significantly reduced by half, indicating that the concentration of the soaking solution has a significant impact on the formation of nanofiltration membrane pores.

[0054] Figure 9 In (a) and (b), the monomer ratio is n. St :n Ip :n AMPS =1:1:0.5, solution concentration is 5%, SEM images differ between 2 and 4 soaking times. As shown in the figures, Figure 9 (a) has a more complex pore distribution, with large and dense pores, while Figure 9(b) The membrane surface appears smoother and flatter in comparison, with smaller and more dispersed pore sizes. This indicates that increasing the number of immersion cycles is beneficial for forming clear and stable nanopores, and the pore distribution tends to be more regular and uniform. This may be because the PVDF filter membrane has fewer immersion cycles, resulting in insufficient quantity and stability of the triblock polymer adhering to the membrane surface, thus failing to form a dense and uniform pore distribution.

[0055] The monomers obtained during preparation are in the following proportions: n St :n Ip :n AMPS A PVDF nanofiltration membrane treated with a ternary block polymer (TBP) at a concentration of 1:1:0.5, a soaking solution concentration of 20%, and four soaking cycles was used to separate and purify porcine spleen fluid to obtain spleen peptide powder. High-resolution mass spectrometry analysis of the spleen peptide powder yielded the following results: Figure 10 The mass spectrum shown indicates the presence of multiple active peptides and small-molecule amino acids, demonstrating the successful separation of these active components from the slurry. Ternary block polymer-modified nanofiltration membranes have significant application research value in the field of pharmaceutical separation and purification.

[0056] The presence of styrene, isoprene, and AMPS structures was confirmed by combining infrared spectroscopy and proton nuclear magnetic resonance spectroscopy, indicating that the polymer polyisoprene-b-polystyrene-b-poly2-acrylamido-2-methylpropanesulfonate sodium salt with a ternary block structure was successfully synthesized by sequential feeding-induced self-assembly.

[0057] Compared with the original PVDF filter membrane, the ternary block polymer composite modified nanofiltration membrane has improved permeation selectivity and stability, and reduced pore size, achieving a nanopore size of 100 nm. St :n Ip :n AMPS A monomer ratio of 1:1:0.5, a solution concentration of 20%, and four soaking cycles are the optimal conditions for preparing nanofiltration membranes according to this invention.

[0058] In the application research of separating and purifying active substances such as spleen peptides from pig spleen slurry, PVDF nanofiltration membranes treated with ternary block polymers can achieve the separation and purification of peptides and other substances.

[0059] This invention uses azobisisobutyronitrile (AIBN) as an initiator, N,N-dimethylformamide (DMF) as a solvent, and sodium 2-acrylamido-2-methylpropanesulfonate (AMPS), styrene (ST), and isoprene (IP) as monomers. Styrene and sodium 2-acrylamido-2-methylpropanesulfonate are copolymerized first by sequential addition, followed by the addition of isoprene monomer to participate in the self-assembly polymerization. By changing the monomer ratio of sodium 2-acrylamido-2-methylpropanesulfonate, polyisoprene-b-polystyrene-b-poly2-acrylamido-2-methylpropanesulfonate (PI-b-PS-b-PAMPS) with different ternary block structures are obtained. The structures of the synthesized products are confirmed by infrared spectroscopy and proton nuclear magnetic resonance spectroscopy. The obtained ternary block polymers are coated onto PVDF filter membranes to prepare composite nanofiltration membranes, and the microstructure of the sample membranes is observed by scanning electron microscopy (SEM). The spleen peptide powder was prepared by separating and purifying porcine spleen serous fluid using the aforementioned ternary block polymer composite nanofiltration membrane. The composition of the spleen peptide powder was analyzed by high-resolution mass spectrometry. The results indicate that the ternary block polymer structure was successfully prepared, and the composite nanofiltration membrane holds promise for achieving pore size control and peptide separation and purification.

[0060] The embodiments described above provide a detailed explanation of the technical solutions and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, additions, and equivalent substitutions made within the scope of the principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a ternary block polymer-modified nanofiltration membrane, characterized in that, Includes the following steps: A ternary block polymer was prepared using sodium 2-acrylamido-2-methylpropanesulfonate, styrene, and isoprene as monomers, DMF as solvent, and AIBN as initiator; the molar ratio of styrene, isoprene, and sodium 2-acrylamido-2-methylpropanesulfonate was 1:1:0.1~0.8; the specific steps included: S1: First, add styrene, sodium 2-acrylamido-2-methylpropanesulfonate solution, AIBN and DMF for copolymerization, stir, reflux, and react for 1~3 h. Then add isoprene to participate in copolymerization and react for 1~3 h. S2: Repeat step S1 more than twice, cool the obtained sample to room temperature to obtain a ternary block polymer solution, remove the organic solvent DMF to obtain the ternary block polymer; S3: Use the ternary block polymer as solute and ethanol as solvent to prepare a 5~20% ternary block polymer-ethanol mixed solution; soak the PVDF microporous filter membrane and then take it out to air dry to obtain a ternary block polymer modified nanofiltration membrane.

2. The method for preparing the ternary block polymer-modified nanofiltration membrane according to claim 1, characterized in that, In step S1, the stirring temperature is 60~85 ℃ and the stirring speed is 10~30 rpm / min.

3. The method for preparing the ternary block polymer-modified nanofiltration membrane according to claim 1, characterized in that, In step S3, the PVDF microporous filter membrane is a PVDF microporous filter membrane after polarization treatment.

4. The method for preparing the ternary block polymer-modified nanofiltration membrane according to claim 1, characterized in that, In step S3, the soaking time is 5-15 minutes; the natural drying time is 3-8 minutes.

5. A ternary block polymer-modified nanofiltration membrane, characterized in that, It is prepared by means of the method described in any one of claims 1-4.

6. The use of the ternary block polymer modified nanofiltration membrane as described in claim 5, characterized in that, The nanofiltration membrane is used for the separation and purification of polypeptide substances.

7. The use of the ternary block polymer modified nanofiltration membrane according to claim 6, characterized in that, The separation and purification steps include: Pig spleen slurry was prepared by crushing, pulping and filtering. The slurry was then separated and purified using a ternary block polymer modified nanofiltration membrane under operating conditions of 0.7~1.5 MPa and 1~40 ℃. After freeze drying, the corresponding spleen peptide powder was obtained.

Citation Information

Patent Citations

  • Anti-pollution separation membrane and preparation method

    CN102728241A

  • Method for preparing porous membrane based on segmented copolymer fibre micel

    CN103120903A